2014
DOI: 10.1016/j.ejmech.2014.07.064
|View full text |Cite
|
Sign up to set email alerts
|

β-amino-alcohol tethered 4-aminoquinoline-isatin conjugates: Synthesis and antimalarial evaluation

Abstract: A series of β-amino alcohol tethered 4-aminoquinoline-isatin conjugates were synthesized with the aim of probing their antimalarial structure activity relationship. Two of the most active conjugates (11b and 11f) exhibited antimalarial efficacy comparable to that of chloroquine, with IC50 values of 11.8 and 13.5 nM, respectively against chloroquine resistant W2 strain of Plasmodium falciparum and are devoid of any cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 51 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Among them, hybrid 96c (IC 50 : 69.0 nM) was comparable to CQ (IC 50 : 60.0 nM) against CQR W2 strain. Replacement of 1,2,3‐triazole linker by piperazinyl‐alkyl ( 97 , IC 50 : 270‐7,520 nM) or piperazinyl‐alkynyl ( 98 , IC 50 : 420‐1120 nM) was harmful to the activity against CQR W2 strain, while β‐amino‐alcohol tethered quinoline‐isatin hybrids 99 (IC 50 : 11.7‐488.1 nM) showed enhanced activity . For hybrids 99 , incorporation of chloro at C‐5 position of isatin moiety could boost up the activity against CQR W2 strain, and even chain lengths were more favorable than the odd chain lengths.…”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, hybrid 96c (IC 50 : 69.0 nM) was comparable to CQ (IC 50 : 60.0 nM) against CQR W2 strain. Replacement of 1,2,3‐triazole linker by piperazinyl‐alkyl ( 97 , IC 50 : 270‐7,520 nM) or piperazinyl‐alkynyl ( 98 , IC 50 : 420‐1120 nM) was harmful to the activity against CQR W2 strain, while β‐amino‐alcohol tethered quinoline‐isatin hybrids 99 (IC 50 : 11.7‐488.1 nM) showed enhanced activity . For hybrids 99 , incorporation of chloro at C‐5 position of isatin moiety could boost up the activity against CQR W2 strain, and even chain lengths were more favorable than the odd chain lengths.…”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 99%
“…For hybrids 99 , incorporation of chloro at C‐5 position of isatin moiety could boost up the activity against CQR W2 strain, and even chain lengths were more favorable than the odd chain lengths. Further study indicated that replacement of diaminoalkyl by piperazinyl ( 100 , IC 50 : 219‐1960 nM) resulted in great loss of activity . Hybrid 99b (IC 50 : 11.7 nM) was 3.1 times more active than CQ (IC 50 : 36.37 nM) against CQR W2 strain, and it was devoid of any cytotoxicity toward HCT116 cells (IC 50 : >20 μM).…”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 99%
“…Compound 14 was found to be most active among piperazine series with an IC 50 value of 216 nM (when R = H) and it was observed that the activity was reduced with the addition of Cl, F or CH 3 at the R position on the phenyl ring. Chloroquine and artemisinin (IC 50 of CQ = 36.37 nM and IC 50 of ART = 4.37 nM, respectively) were used as a standard drug for comparison [Nisha et al, 2014]. Compounds 15 and 16 showed potent antimalarial activity against the CQR W2 strain of P. falciparum with IC 50 values of 5.6 and 17.3 nM respectively, while CQ was used as a standard drug with IC 50 of 382 nM.…”
Section: Potent Side Chain Variant Quinoline Based Antimalarial Agentsmentioning
confidence: 99%
“…Kumar et al synthesized a library of isatin-7-chloroquinoline conjugates linked by 1H-1,2,3-triazole moiety along with assessment of their antiplasmodial proles (Scheme 15). The tested compounds (88) were devoid of antiplasmodial activity, while 89, having an alkyl chain between isatin and 7-chloroquinoline moieties, displayed enhancement in antiplasmodial potency. Activity was found to depend on the C-5 substituent of the isatin ring and on the alkyl chain length between the isatin and 7-chloroquinoline moieties.…”
Section: -Aminoquinoline-isatin Conjugatesmentioning
confidence: 99%
“…13) displayed antiplasmodial potency comparable to that of CQ, with IC 50 values of 11.7 and 13.5 nM, against the W2 resistant strain of P. falciparum. 88…”
Section: -Aminoquinoline-isatin Conjugatesmentioning
confidence: 99%